2006
DOI: 10.1190/1.2208263
|View full text |Cite
|
Sign up to set email alerts
|

Teleseismic shot-profile migration

Abstract: Lithospheric images generated from multi-channel teleseismic data reveal important aspects of crustal and mantle structure, and offer windows into past and present tectonic processes. However, the imaging techniques used to generate these images can be improved through further adaption of exploration seismology practices. We introduce the shot-profile representation of wave-equation migration as a novel way to cast the teleseismic imaging problem. We show how this technique can be tailored to suit teleseismic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Our common‐conversion‐point (CRP) approach for teleseismic SH reverberation analysis is simple to implement and appears to give robust results for the USArray data set. However, our method likely could be improved in a number of ways: Bootstrap resampling of the waveforms would provide a measure of the statistical significance of any observed reflections and could be used to replace our requirement of at least 200 seismograms to display the result. In principle, migration approaches, such as those described by Pavlis (), Shang et al (), Shragge et al (), and Burdick et al () for receiver functions and/or free‐surface multiples, could be applied to better image dipping structures. However, migration methods work best with uniform data coverage, so the very uneven distribution of earthquake sources may present challenges. More comprehensive testing of corrections for 3‐D velocity structure would help to better understand their sensitivity to specific tomography models and how they can change the coherence of the image.…”
Section: Discussionmentioning
confidence: 99%
“…Our common‐conversion‐point (CRP) approach for teleseismic SH reverberation analysis is simple to implement and appears to give robust results for the USArray data set. However, our method likely could be improved in a number of ways: Bootstrap resampling of the waveforms would provide a measure of the statistical significance of any observed reflections and could be used to replace our requirement of at least 200 seismograms to display the result. In principle, migration approaches, such as those described by Pavlis (), Shang et al (), Shragge et al (), and Burdick et al () for receiver functions and/or free‐surface multiples, could be applied to better image dipping structures. However, migration methods work best with uniform data coverage, so the very uneven distribution of earthquake sources may present challenges. More comprehensive testing of corrections for 3‐D velocity structure would help to better understand their sensitivity to specific tomography models and how they can change the coherence of the image.…”
Section: Discussionmentioning
confidence: 99%
“…Teleseismic array imaging based on converted and scattered waves is one of the essential tools for investigating the crustal and upper mantle structures, and has contributed significantly over the past three decades to our understanding of tectonic evolution and internal geodynamic processes [e.g., Rondenay, 2009;Kind et al, 2012;Liu and Gu, 2012]. Various methods including receiver function (RF) analysis through single station stacking [e.g., Langston, 1977;Yan and Clayton, 2007], common conversion point (CCP) stacking [e.g., Revenaugh, 1995;Sheehan et al, 2000;Chen et al, 2005], inverse scattering approaches based on asymptotic methods such as generalized Radon transform [e.g., Bostock et al, 2001;Cao et al, 2010;Shang et al, 2014], teleseismic migration [e.g., Shragge et al, 2006;Shang et al, 2012], and teleseismic scattering tomography [e.g., Frederiksen and Revenaugh, 2004;Pageot et al, 2013;Burdick et al, 2014;Tong et al, 2014] have been developed for specific imaging purposes. RF analysis is a routine tool to characterize major discontinuities of the Earth's subsurface such as the Moho, 410 km and 660 km discontinuities [e.g., Rondenay, 2009;Kind et al, 2012].…”
Section: Introductionmentioning
confidence: 99%
“…Artman et al ͑2004͒ provided the mathematical justification for zero-phase source functions. Shragge et al ͑2006͒ showed results for the special case of imaging with teleseisms. Direct migration of transmission wavefields requires an imaging algorithm composed of wavefield extrapolation and a correlation-based imaging condition.…”
Section: Direct Migrationmentioning
confidence: 97%